Respostas

  • Ind
  • Ambicioso
2013-12-07T22:05:43-02:00
Condição para retas perpendiculares : a1. a2 = -1, onde a1 = coeficiente angular da reta 1 e a2 = coeficiente angular da reta 2 

I) Reta s : y = a.x + b , P(3,4) --> P(x,y)
4 = a.3 +b

II) Reta t : 3y + 2x - 4 
y =  \frac{-2x + 4}{3}  
a2 =  \frac{-2}{ 3}

III) a1 . a2 = -1
a1. \frac{-2}{3} = -1

a1 =  \frac{2}{3} - 1

a1 =  \frac{-1}{3}

IV) Reta s : 4 = 3a+ b
4 = 3. \frac{-1}{3} +b
b = 4+ 1
b = 5 

Reta s : Y =  \frac{-1}{3}x + 5
1 5 1